"Continually Reminded of Their Inferior Position”: Social Dominance, Implicit Bias, Criminality, and Race - Darren L. Hutchinson (Washington University Journal of Law & Policy, 2015)
This Article contends that implicit bias theory has improved contemporary understanding of the dynamics of individual bias. Implicit bias research has also helped to explain the persistent racial disparities in many areas of public policy, including criminal law and enforcement. Implicit bias theory, however, does not provide the foundation for a comprehensive analysis of racial inequality. Even if implicit racial biases exist pervasively, these biases alone do not explain broad societal tolerance of vast racial inequality. Instead, as social dominance theorists have found, a strong desire among powerful classes to preserve the benefits they receive from stratification leads to collective acceptance of group-based inequality. Because racial inequality within criminal law and enforcement reinforces the vulnerability of persons of color and replicates historical injuries caused by explicitly racist practices, legal theorists whose work analyzes the intersection of criminality and racial subordination could find that social dominance theory allows for a rich discussion of these issues.
Keywords: Darren Hutchinson; implicit bias theory; racial inequality